The Integration of Technology and Humanism Rooted in Islamic Values: A Strategy for Strengthening Deep Learning in the Era of Smart Society 5.0 - Hanifah, Alif Nur; Widiyastutik, Dini; Nitoqoin, Dzatan; Zainiyati, Husniyatus Salamah; Asrohah, Hanun (Jurnal Pendidikan Islam, 2026)
Global issues regarding the threat of technology potentially replacing the role of teachers and concerns about the loss of humanism and the degradation of student manners due to the dominance of digital interactions have triggered deep anxiety among educators and parents. The shift in the global education paradigm towards Deep Learning requires learning experiences that go beyond the transfer of knowledge. This includes the dimensions of mindfulness, meaningfulness, and joyfulness. However, in the era of Smart Society 5.0, we are often confronted with the contradictory reality that easy access to information actually degrades critical thinking and morality. This study aims to formulate a strategy for integrating Techno-Humanism within the framework of Islamic Education to strengthen the quality of deep learning while addressing concerns about the disruption of the teacher's role. Using the library research method with synthesis analysis of primary pedagogical literature and reputable journal articles from the last five years (2020–2025), this study deconstructs the dichotomy between humans and machines. The findings of this study offer integration strategies through three main mechanisms: (1) Integration of the cognitive domain by transforming AI into a verified logical partner through the concept of Tabayyun, (2) Integration of the contextual domain through the use of IoT to strengthen the role of Khalifah fil Ardh (social-environmental awareness social-environmental concern), and (3) Integration of the affective domain by making technology a canvas for expression that is emotionally validated by teachers as Murabbi.